PENGARUH MOTIVASI FINANSIAL DAN NON FINANSIAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN HOTEL ADI DHARMA KUTA BALI - I Gusti Agung Istri Maruti Putri; Ni Nyoman Menuh (Forum Manajemen STIMI Handayani Denpasar, 2018)
A good hotel operational is based on good hotel management, so itminimize operational mistakes. A good hotel management supported by humanresources, work environment, work spirit, and good work discipline as well. All theseelements together will create a conducive working atmosphere in the management ofa hotel. This research was conducted to find out the influence of financian and nonfinancial motvation to work produktivity of employees in Adi Dharma Kuta Bali. Thisresearch This research used correlation regression analysis method. The samples ofresearch were employees of Adi Dharma Hotel Kuta amounted to33 people, eachgiven questionnaires according to the variables. Further data was analyzed using partial F test to see the effect of all variables simultaneously. From result of research got significant 0,000 which means that financial and non financial motivation hada significant effect on employee produktivity (p <0,05). The result of t test analysisis non financial moivation has a positive and significant effect on employee workproductivity, while the financial motivation has no significant effect on employeework productivity.